Influence on The Level Riders Motorcycle Accident Traffic with Traffic Methods of Conflict Technique (TCT) (Case Study: Jalan Raya Narogong Bekasi City) - Rifai, Andri Irfan; Fernanda, Finsa Aziz (NAROTAMA UNIVERSITY, Indonesia, 2020)
The increasing number of traffic accidents can be caused by drivers, vehicles, highways, and the environment. In Indonesia, traffic accidents become one of the problems in the transportation sector. Prevention is done during this time to anticipate accidents only based on the data of the accident quantity that has occurred. Though factors or incidents that can cause accidents to become the biggest contributor in the event of accidents. For example, driving a vehicle in an unorderly manner, the pace of the vehicle with the above-average velocity set traffic rules, and sudden vehicle maneuvers. This research is done by identifying and analyzing the behavior of motorcyclists who affect accidents and applying TCT methods to observation data at points that become potential locations Against accidents. The research location is on the Narogong Highway which is divided into 2 segments. In Segment 1 begins at junction four Cipendawa (after the flyover Simpang Cipendawa) until the junction of the three Gg. Sawo (Bantar Gebang Market). Next, in Segment 2 starts from junction three of Gg. Sawo (Bantar Gebang Market) until the three houses of Vida housing. The results showed that the research location had potential that could cause the accident to be front-side on the first order, collision front-front on the second-order, and side-by-side collision on the third order. The speed of vehicles has an impact on accidents.